Advantage of a Narrow Spectrum Host Defense (Antimicrobial) Peptide Over a Broad Spectrum Analog in Preclinical Drug Development - Ostorhazi, Eszter; Hoffmann, Ralf; Herth, Nicole; Wade, John D.; Kraus, Carl N.; Otvos Jr., Laszlo (Frontiers in Chemistry, 2018)
The APO-type proline-arginine-rich host defense peptides exhibit potent in vitro killing parameters against Enterobacteriaceae but not to other bacteria. Because of the excellent in vivo properties against systemic and local infections, attempts are regularly made to further improve the activity spectrum. A C-terminal hydrazide analog of the Chex1-Arg20 amide (ARV-1502) shows somewhat improved minimal inhibitory concentration against Moraxellaceae. Here we compared the activity of the two peptides as well as an inactive dimeric reverse amide analog in a systemic Acinetobacter baumannii infection. Only the narrow spectrum amide derivative reduced the 6-h blood bacterial burden by >2 log10 units reaching statistical significance (p=0.03 at 5 mg/kg and 0.031 at 2 mg/kg administered intramuscularly). The hydrazide derivative, probably due to stronger activity on cell membranes, lysed erythrocytes at lower concentrations, and caused toxic effects at lower doses (10 mg/kg vs 25 mg/kg). In a limited study, the amide induced a >5-fold production of the anti-inflammatory cytokine IL-10 over untreated naïve mice and minor increases in the anti-inflammatory IL-4 and pro-inflammatory cytokines TNF-α and IL-6, in blood. The blood of hydrazide-treated mice exhibited significantly lowered levels of IL-10 and slightly decreased IL-4 and TNF-α. These results suggest that the improved efficacy of the narrow-spectrum amide analog is likely associated with increased anti-inflammatory cytokine production and better stimulation of the immune system. Although blood IL-6 and TNF-α levels are frequently used as markers of potential toxicity in drug development, we did not observe any notable increase in mice receiving the toxic polyamide antibiotic colistin.